The use of weaponized kites and balloons in the Israeli – Palestinian conflict - Joanna Zych (Security and Defence Quarterly, 2019)
Objectives The aim of this paper is to analyse the use of weaponised incendiary kites and helium balloons in the Israeli-Palestinian hostilities between March and December 2018. The paper argues that arson started with incendiary kites and balloons can easily be exploited for terrorist purposes and poses a serious challenge for regular armed forces and for civilian emergency services.